Depressive symptoms in patients referred for clinical amyloid PET imaging. (31st December 2021) - Loreto, Flavia; Fitzgerald, Anna; Golemme, Mara; Win, Zarni; Patel, Neva; Gunning, Stephen; Gontsarova, Anastasia; Kennedy, Angus; Edison, Paul; Carswell, Christopher J; Perry, Richard J; Malhotra, Paresh A
Abstract: Background: The clinical use of amyloid‐PET imaging (API) is guided by a set of published appropriate use criteria (Johnson et al., 2013). Patients meeting these criteria have suspected Alzheimer's Disease (AD) accompanied by an atypical clinical presentation leading to substantial diagnostic uncertainty. Previous large‐cohort studies have investigated this clinical population from a diagnostic standpoint, looking at the impact of using amyloid‐PET to elucidate the aetiology of impairment. However, data concerning their clinical phenotypes is lacking. In this study, we investigated the prevalence of depression and its association with Alzheimer's pathology in Memory Clinic patients who received clinical API. Method: We reviewed the clinical records of 185 older adults (mean age 67.09±9.35, 49% females) who were assessed in our Clinic between January 2017 and June 2019 and received API. Referral to amyloid‐PET followed a multidisciplinary meeting and was in line with appropriate use criteria. Patients were categorised as 'D+', with history of depression, if they had received a previous depression diagnosis and/or if they had a history of depressive symptoms. Overall depression prevalence was compared with published cohort data. Amyloid‐PET results (positive versus negative) were compared between the D+ and the D‐ (without history of depression) groups. In D+ patients, we determined the onset and status of depressive symptoms. Result: Of 185 patients, 98 (53%) had a history of depression. Of these, 89 individuals had ongoing symptoms at the time of referral to our Clinic and 59 of them were on antidepressants. The mean age of depression onset was 58.25(±12.25) years. Depression prevalence in this cohort was considerably higher than that generally seen in memory clinics (20%; Knapskog et al., 2014) and in healthy older adults (19%; McDougall et al., 2017). Depression history was not associated with amyloid‐PET results (%positive: D+ 39.8%, D‐ 50.6%, χ 2 (1)=2.16 p=.14), age (mean±SD: D+ 66.47±9.03 years, D‐ 67.79±9.71 years, t(183)=‐.95 p=.342), or sex (%female: D+ 44.9%, D‐ 52.9%, χ 2 (1)=.1.17 p=.304). Conclusion: Depression prevalence is high in patients referred for clinical amyloid‐PET imaging and is independent of the presence or absence of Alzheimer's pathology. Depression may be one of the key contributors to diagnostic uncertainty in this group.